(untitled) (Revista Nacional de Odontología, 2015)
Introduction: This study aimed to compare the cephalometric values found in patients of the Faculty of Dentistry of the University of Antioquia (Colombia) and the values reported in the study performed at the University of Michigan, USA, by Riolo et al. in 1974. Materials and methods: Retrospective comparative non-experimental study with a sample of 204 cephalic side X-rays (127 women and 77 men) of patients diagnosed with Type I malocclusion with no previous treatment, from 7 to 11 years of age, traced by a single operator. The gathered information was digitalized, the media and the standard deviation were calculated to each variable by age and gender. To establish statistically significant differences, the non-parametric Mann Whitney U test (α=0.05) was applied. The results obtained were compared to the study of Riolo et al. (1974) in 83 individuals (36 women and 47 men), the similarities or differences among them were determined, as well as the cephalometric variables different than the used standards. Results and conclusions: 26 cephalometric variables were observed, the results showed more differences than similarities among the found values and the values deemed standard, statistically significant sexual dimorphism was observed in 11 variables. The variables in which the use of Riolo et al.’s standards is still advisable are reported, as well as the variables in which it is not recommended, based on the comparison performed.